Metabolic surgery improves renal injury independent of weight loss: a meta-analysis - Scheurlen, Katharina; Probst, Pascal; Kopf, Stefan; Nawroth, Peter Paul; Billeter, Adrian; Müller, Beat P. (Surgery for obesity and related diseases, 2019)
Background - Metabolic surgery is the most effective therapy for patients with type 2 diabetes (T2D), also improving diabetic kidney disease. Whether these effects depend on weight loss is currently unknown. - Objectives - To assess the correlation between weight loss and improvement of diabetic kidney disease in patients with T2D undergoing metabolic surgery. - Setting - University of Heidelberg, Germany. - Methods - A systematic literature search was performed in December 2018 using the MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials databases without language restrictions or time limit. Studies reporting exact data on change in urinary albumin-creatinine ratio (uACR) or albuminuria as well as change in body mass index in patients with T2D undergoing metabolic surgery were included. Out of 2145 potentially eligible hits, 15 studies were included. Study quality was assessed using the Downs and Black score. Data were pooled using a random-effects model, and a Spearman’s rank correlation was performed. - Results - No correlation was found between improved renal injury (change in uACR or albuminuria) and weight loss (change in body mass index) (rs = -.306, P = 0.504, and rs = -.086, P = .872), and no significant correlation was found between improved renal injury (change in uACR or albuminuria) and improved glycemic control (change in A1C) (rs = .378, P = .403, and rs = .500, P = .391. - Conclusion - Metabolic surgery can improve diabetic kidney disease independent of weight loss and glycemic control. Other mechanisms, including modified adipokine balance, signaling pathways of fat tissue and gut hormones, or reduced systemic inflammation, contribute to improved renal injury, while weight loss seems to play a lesser role than expected.
Gesehen am 11.12.2019